Implementasi Augmented Reality Berbasis Plane Detection Untuk Meningkatkan Promosi Sekolah - Fatimah, Dini Destiani Siti; Pariyatin, Yeni; Nursyahidah, Adhya (Institut Teknologi Garut, 2025)
The rapid development of information technology has brought many changes in various fields, including education. One technology that is beginning to be widely applied is Augmented Reality (AR). This study aims to create an AR-based school promotion application using the plane detection method in a vocational high school. This application displays 3D models of school facilities, such as classrooms, RPL practice rooms, fashion design practice rooms, and mosques. All objects can be viewed directly through a flat surface without the need for markers. The development of this application uses the Multimedia Development Life Cycle (MDLC) method with six stages. Testing was conducted through alpha and beta testing. Alpha testing showed that all application features worked well without any obstacles. Meanwhile, beta testing used the System Usability Scale (SUS) method and produced an average score of 81.87, which falls into the “Good” category, meaning that the application is easy to use and accepted by users. This application is considered suitable for use as an interactive and attractive school promotion medium.